Assessing disparities in medical students’ knowledge and attitude about monkeypox: a cross-sectional study of 27 countries across three continents - Abd ElHafeez, Samar; Gebreal, Assem; Khalil, Mohammad Adnan; Youssef, Naglaa; Sallam, Malik; Elshabrawy, Abdelhamid; Abdel-Rahman, Suzan; Mahboob, Amira Saad; Yazbek, Saja; Elbanna, Eman H.; Adhyaru, Riddhi; Rodoshi, Zarin Nudar; et al. (Frontiers in Public Health, 2023)
The recent Monkeypox (Mpox) outbreak confirmed by the World Health Organization (WHO) underscores the importance of evaluating the knowledge and attitude of medical students toward emerging diseases, given their potential roles as healthcare professionals and sources of public information during outbreaks. This study aimed to assess medical students' knowledge and attitude about Mpox and to identify factors affecting their level of knowledge and attitude in low-income and high-income countries.A cross-sectional study was conducted on 11,919 medical students from 27 countries. A newlydeveloped validated questionnaire was used to collect data on knowledge (14 items), attitude ( 12items), and baseline criteria. The relationship between a range of factors and knowledge and attitude was studied using univariate and multivariate analyses.46% of the study participants were males; 10.7% were in their sixth year; 54.6% knew about smallpox; 84% received the COVID-19 vaccine; and 12.5% had training on Mpox. 55.3% had good knowledge of Mpox and 51.7% had a positive attitude towards it. Male medical students in their third, fifth, or sixth year, and from high-income countries were predictors of good knowledge about Mpox. They acquired information on Mpox from social media and scientific websites. Male medical students: residing in urban areas; who were employed; were in their fifth year; had received Mpox training; had knowledge about smallpox and the COVID-19 vaccine; and who received information from reliable sources were the predictors of a positive attitude towards Mpox.There were differences in knowledge and attitude towards Mpox between medical students in low and high-income countries, emphasizing the need for incorporating epidemiology of re-emerging diseases like Mpox into the medical curriculum to improve disease prevention and control.